2013
DOI: 10.1016/j.jep.2012.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory activity of polysaccharides isolated from Alchornea cordifolia

Abstract: Ethnopharmacological relevance Extracts of leaves from different species of the genus Alchornea have been used for centuries to treat a variety of medicinal problems in tropical Africa. However, little is known about the high-molecular weight active components conferring therapeutic properties to these extracts. Objective The aim of this study was to evaluate the immunomodulatory activity of polysaccharides isolated from the leaves of Alchornea cordifolia. Materials and methods Water-soluble polysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 50 publications
1
31
0
4
Order By: Relevance
“…3E, among the tested dosage, LJP-31 dose-dependently resulted in an increase of IL-10 production as well as TNF-␣, IL-1␤ and IL-6. These results are consistent with the effects of some other polysaccharides on the cytokine production by macrophages (Zhang & Dai, 2011;Kim et al, 2012;Kouakou et al, 2013). It has been reported that the macrophages are able to be converted into M1 cells and M2 cells when exposed to various stimulators.…”
Section: Ljp-31 Induces No Tnf-˛ Il-1ˇ Il-6 and Il-10 Production Bsupporting
confidence: 91%
“…3E, among the tested dosage, LJP-31 dose-dependently resulted in an increase of IL-10 production as well as TNF-␣, IL-1␤ and IL-6. These results are consistent with the effects of some other polysaccharides on the cytokine production by macrophages (Zhang & Dai, 2011;Kim et al, 2012;Kouakou et al, 2013). It has been reported that the macrophages are able to be converted into M1 cells and M2 cells when exposed to various stimulators.…”
Section: Ljp-31 Induces No Tnf-˛ Il-1ˇ Il-6 and Il-10 Production Bsupporting
confidence: 91%
“…Phagocytic ratio showed the macrophages amount in 100 macrophages which actively phagocyted latex, while phagocytic Index showed the number of latex which were phagocyted by 100 macrophages. According to Kouakou et al (2013), a common feature of plant polysaccharides that modulate macrophage function may be higher molecular weight as were found previously from some researchs (Schepetkin et al, 2008;Xie et al, 2007;and Xie et al, 2008) that immunomodulatory activity positively correlated with increased molecular weight of various plant polysaccharides. It has been reported that polysaccharides are able to bind to phenolic substances by intermolecular interactions (Renard et al, 2001), which changing the molecular conformation of carbohydrates.…”
Section: Results Of Immunostimulatory Effects Of Yielded Fractionsmentioning
confidence: 74%
“…PBMCs were pre-incubated with the vitamin K antagonist for 30 min before the cells were stimulated with PHA for 48 h. The cytokines secreted into the supernatants were analyzed by ELISA. Also, in a recent report cytokine secretion and activation of mitogen-activated protein kinases (MAPK) in response to polysaccharides isolated from Alchornea cordifolia (Kouakou et al 2013 ) was studied. Evaluation of the effects of polysaccharides on the activation status of an array of different MAPKs was done using a phospho-MAPK kit.…”
Section: Experimental Read Outmentioning
confidence: 99%